Pengawasan Pembangunan Jalan Desa Air Putih Ilir Kecamatan Plakat Tinggi Kabupaten Musi Banyuasin - Arisandi, Desi; Syuroh, Mat; Mudasir, Mudasir (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This research aims to evaluate the supervision of road construction in Air Putih Ilir Village, Plakat Tinggi District, Musi Banyuasin Regency. This research is qualitative in nature, with qualitative data obtained through interviews with informants and analysis of relevant documents. The research results show that although supervision of road construction in Air Putih Ilir Village, Plakat Tinggi District, Musi Banyuasin Regency has been carried out, it has still not reached the optimal level. This is caused by several factors, including a lack of knowledge and skills of supervisory officers, as well as limited funds available. This lack of funding also results in a lack of equipment and facilities that support the work of monitoring officers, such as vehicles that are often damaged. On the planning side, the lack of knowledge and ability of officers as supervisors is one of the obstacles. In implementation, the lack of information from field implementers is also a problem, because they feel that there are people who are more competent in answering questions. In addition, the low quality of construction materials results in rapid road damage, and there is also road construction that is not in accordance with the wishes of the community. Regarding reporting, the Audit Results Report has been prepared, but is often delivered late due to delays in submitting the report from the implementing party. This is because there are still deficiencies in collecting the required data and documents, so it requires additional time to complete them.